FAKTOR – FAKTOR YANG MEMPENGARUHI PELAKSANAAN PROGRAM PEMBERDAYAAN MASYARAKAT DI KOTA PEKANBARU (Studi Usaha Ekonomi Kelurahan) - Suri, Dia Meirina; Nurmasari, Nurmasari (UIR PRESS, 2018)
The purpose of this study is to analyze the factors that influence the implementation of community empowerment in Pekanbaru City (Study of Economic Village Business Program). This research method using qualitative descriptive approach with qualitative analysis technique triangulation technique.The results of the study found that the implementation of Urban Economic Village program in Pekanbaru City is influenced by standard and objective factors, resources, observation activities and interorganizational communication, implementing characteristics, disposition / attitude of executor and economic, social and political conditions. Kelurahan maharatu implement well the program implementation standards, have the human resources who want to work in accordance with their duties, while the village of West Sidomulyo and Tanah Datar has not implemented the program in accordance with the standards and policy objectives other than the resources held are not responsible for the tasks that must be implemented, so that the implementation of the Village Economic Business program is not going well.